2014
DOI: 10.1007/s10974-014-9402-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the sarco/endoplasmic reticulum Ca2+-ATPase (SERCA1) by rutin derivatives

Abstract: The effect of lipophilic rutin derivatives (acylated with fatty acid chain length of 16-22) on sarco/endoplasmic reticulum Ca(2+)-ATPase (SERCA1 isoform) compared to the parent molecule rutin was evaluated. Rutin derivatives caused concentration dependent decrease of SERCA1 activity (IC50 ~ 23-64 µM) and significant conformational alterations in the transmembrane region of the enzyme. Upon treatment by peroxynitrite, rutin derivatives exerted a hormetic effect, i.e. prevented enzyme activity decrease at low co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 66 publications
(61 reference statements)
1
14
0
Order By: Relevance
“…In agreement with our previous results [33], the starting structure of RA complex with SERCA1a was based on the crystal structure of E2 state free from exogenous inhibitors, ATP and calcium ions (Toyoshima et al, 2013, Protein Data Bank (PDB); http://www.rcsb.org; PDB ID 3w5c). The PDB model of E2 state was chosen based on partial structural similarity with the compounds identified as SERCA1a E2 state inhibitors (thapsigargine and nonylphenol) [16], as well as according to the long lipophilic chain of RA.…”
Section: Starting Structure Of Serca1a-ra Complexsupporting
confidence: 68%
See 2 more Smart Citations
“…In agreement with our previous results [33], the starting structure of RA complex with SERCA1a was based on the crystal structure of E2 state free from exogenous inhibitors, ATP and calcium ions (Toyoshima et al, 2013, Protein Data Bank (PDB); http://www.rcsb.org; PDB ID 3w5c). The PDB model of E2 state was chosen based on partial structural similarity with the compounds identified as SERCA1a E2 state inhibitors (thapsigargine and nonylphenol) [16], as well as according to the long lipophilic chain of RA.…”
Section: Starting Structure Of Serca1a-ra Complexsupporting
confidence: 68%
“…As the experimentally tested rutin derivatives brought new structural features (e.g., long fatty acid chain) into the diversity of SERCA inhibitors as described above, we reasoned to perform a molecular dynamics simulation study to elucidate the mechanism of action of the most effective inhibitor of the series, rutin arachidonate [33] (see Figure 1). Our results predicted that the binding of rutin arachidonate towards SERCA1a occurs in the vicinity of the binding site of calcium ions (transmembrane region) and near the location of the well-known inhibitor thapsigargin.…”
Section: Bilayer Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The posttranslational modifications of SERCA1 by rutin esters include a significant loss of free sufhydryl groups, the protection of the enzyme from protein carbonyl formation, and the prevention of SERCA from tyrosinase (except R20:4 and R22:1). The inhibitory activity of the rutin esters is probably due to the interaction of these compounds with Glu771, a residue involved in Ca 2+ binding [132].…”
Section: Enzyme Inhibitorsmentioning
confidence: 99%
“…Recently, the research studies on rutin revealed the effectiveness of this drug in treating cerebral ischemia (Annapurna et al, 2013[6]; Zhang et al, 2013[25]; Jang et al, 2014[13]; Rodrigues et al, 2013[18]; Khan et al, 2009[14]; Raza et al, 2011[17]), however a major problem of low water solubility hence low bioavailability still exist with rutin (Park et al, 2013[16]; Veselova et al, 2012[21]; Sasikala et al, 2013[19]). In addition, literature studies report rutin, a drug with lipophilic property (Baldisserotto et al, 2015[7]; Viskupicová et al, 2015[22]) and thus it is a well-known fact that oral delivery of lipophilic drugs including rutin encounters different problems such as i) permeability complications leading to poor bioavailability ii) more prone to chemical and enzymatic degradation in the gastrointestinal tract, and iii) extensive hepatic first-pass metabolism. The complications aforementioned necessitate effective solution in the form of intranasal drug administration for targeted therapy in brain with numerous advantages, i.e.…”
Section: Introductionmentioning
confidence: 99%